How do age and sex influence pain threshold and tolerance among Santal tribal people living in West Bengal, India? - Arpita Santra; Subrata Kumar Roy; Monali Goswami; Diptendu Chatterjee (Anthropological Review)
The perception of pain, encompassing pain threshold and tolerance levels, is a complex phenomenon influenced by biological, psychological, and sociocultural factors. Notably, age and sex have consistently emerged as pivotal determinants in modulating pain perception. The study aimed to examine age and sex differences in pain threshold and tolerance levels. Furthermore, it delved into exploring whether age-related differences in pain threshold and tolerance levels vary between males and females. This study incorporated 484 healthy Santal tribal individuals aged 18–88 years (male 203 and female 281) living in Howrah and Purba Bardhaman Districts of West Bengal State, India, who reported no chronic or significant pain at the time of data collection. Pain threshold and tolerance levels were assessed using a digital algometer. Results of two-way ANOVA revealed significant main effects of age and sex on every pain threshold and tolerance level assessed in this study, indicating that older individuals had lower pain threshold and tolerance levels than younger ones. Males demonstrated greater levels of pain threshold and tolerance relative to females. Age and sex showed a significant interaction effect on pain tolerance levels, but not on pain threshold levels demonstrating the age-associated declining trend in pain threshold levels was consistent for either sex; however, such a tendency in pain tolerance levels was more pronounced in men. These findings highlight the importance of considering age and sex factors when assessing pain perception.